2018
DOI: 10.1002/srin.201800447
|View full text |Cite
|
Sign up to set email alerts
|

In‐Depth Oxide Scale Growth Analysis of B and Ti Microalloyed AISI 304 in Oxygen‐Containing Furnace Atmospheres and CH4 Burn‐Simulating Furnace Atmospheres

Abstract: The effects of boron and titanium microalloying on scale‐layer formation and structure on AISI 304 austenitic stainless steel are studied. The research is focused on a steel slab's oxide scale formation in a reheat furnace prior to hot rolling. The studied boron microalloying amounts are 7, 35, and 55 ppm and the studied titanium microalloying amounts are <100 and 400 ppm. In‐depth temperature and atmosphere tests span from 1100 to 1300 °C for an O2‐containing atmosphere and 1100 to 1250 °C in an H2O‐containin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…The sodium sulfate concentration of electrolyte solution used in study was significantly lower than the electrolyte concentration used at the industrial pickling plant. 2,18 To estimate the factorial effect of each parameter, the results were analyzed using Equation (6), in which the average current efficiency of samples with high parameters (+) are compared to samples with low parameters (−).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The sodium sulfate concentration of electrolyte solution used in study was significantly lower than the electrolyte concentration used at the industrial pickling plant. 2,18 To estimate the factorial effect of each parameter, the results were analyzed using Equation (6), in which the average current efficiency of samples with high parameters (+) are compared to samples with low parameters (−).…”
Section: Methodsmentioning
confidence: 99%
“…1 During production, stainless steel is heated, and a scale consisting of several elements including chromium, iron, manganese, nickel, silica, and others, is formed, depending on the alloying of stainless steel. [2][3][4][5] At first, the oxide phase mainly consists of chromium oxide, with lesser amounts of other oxides as pointed out by an anonymous peer reviewer. As the scale thickens, phase of mixed oxides is formed.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The complexity of such RICHARD scale structures has been reported for different steel compositions, such as low to medium carbon steels, [4,6,[15][16][17][18] ferritic stainless steels, [19][20][21] and austenitic stainless steels. [7,[22][23][24][25] These high temperature oxidation studies were performed to document the scale growth kinetics and the mechanisms of scale formation. Characterization of the scale was performed using scanning electron microscopy coupled with energy-dispersive X-ray (SEM/EDX), Raman spectroscopy, transmission electron microscopy (TEM), and X-ray diffraction to document microstructure, chemistry, and oxide phases present in the scale layers for the different steels.…”
Section: Introductionmentioning
confidence: 99%
“…Asai et al reported that the addition of nickel (Ni) also reduced the scale removability. Laukka et al found that above 1225 °C in an O 2 atmosphere, oxide growth increased in the presence of boron (B), but reduced by titanium (Ti) addition.…”
Section: Introductionmentioning
confidence: 99%